Maturidade, reprodução e estrutura populacional do caranguejo Anomura Aegla marginata Bond-Buckup & Buckup, 1994: (Crustacea: Decapoda) - Silva, Alexandre Ribeiro [UNESP] (2015)
This work's objective consists in to verify the maturity, reproduction and population structure of Aegla marginata sampled in Intervales State Park, São Paulo state. Morphometric characteristics such as sexual dimorphism and allometric growth were investigated from a materiel sampled in the years of 1999, 2000 and 2006. The population aspects of its biology were analyzed from monthly samples of October 2013 from December 2014 using baited traps. The reproductive period was determined through observation of ovigerous females (bearing impregnated eggs or bearing embryos added to the pleopods), and the recruitment was determined from the observation of small individuals (juveniles) in the population. Ovigerous females were taken to the laboratory where its eggs were counted for fecundity purposes. Fifteen eggs were randomly selected and photographed through an image system for measurement of its axis with the intuit to obtain its volume, and finally both eggs and females were dried for reproductive output purposes. It was observed a latitudinal trend in eglids species related to its reproduction and fecundity, was also seen a relationship between reproductive period and temperature. Males and females presented sexual dimorphism due energy allocation during its ontogenetic growth. Males showed a hyperallometric growth for chelae measures, this is because their agonistic behavior and also larger males are favored in mating. Females showed hyperallometry for abdomen measures, increasing its reproductive efficiency. Aegla marginata had a reproductive period of eight months with a peak during the late autumn and winter, which corroborates the latitudinal pattern for the species of the same genus. Sexual maturity base in CC50 was 9.28 of carapace length for females. Thirty and two ovigerous females were analysed, being 17 with embryos in initial stage, 10 intermediary and five in final stage. The number of embry...